N-terminal pyroglutamate formation in CX3CL1 is essential for its full biologic activity. Issue 4 (24th August 2017) - Kehlen, Astrid; Haegele, Monique; Böhme, Livia; Cynis, Holger; Hoffmann, Torsten; Demuth, Hans-Ulrich
Abstract : CX3CL1 (fractalkine) is a unique member of the CX3C chemokine family and mediates both adhesion and cell migration in inflammatory processes. Frequently, the activity of chemokines depends on a modified N-terminus as described for the N-terminus of CCL2 modified to a pGlu- (pyroglutamate) residue by QC (glutaminyl cyclase) activity. Here, we assess the role of the pGlu-modified residue of the CX3CL1 chemokine domain in human endothelial and smooth muscle cells. For the first time, we demonstrated using MS that QC ( QPCT, gene name of QC) or its isoenzyme isoQC (iso-glutaminyl cyclase) ( QPCTL, gene name of isoQC) catalyse the formation of N-terminal-modified pGlu-CX3CL1. Expression of QPCT is co-regulated with its substrates CCL2 and CX3CL1 in HUVECs (human umbilical vein endothelial cells) and HCASMCs (human coronary artery smooth muscle cells) upon stimulation with TNF-α and IL-1β whereas QPCTL expression is not affected. By contrast, inhibition of the NF-κB pathway using an IKK2 inhibitor decreased the expression of the co-regulated targets QPCT, CCL2, and CX3CL1 . Furthermore, RNAi-mediated inhibition of QPCT expression resulted in a reduction in CCL2 and CX3CL1 mRNA. In HCASMCs, N-terminal-modified pGlu1-CX3CL1 induced a significant stronger effect on phosphorylation of ERK (extracellular signal regulated kinase) 1/2, Akt (protein kinase B), and p38 (p38 mitogen-activated protein kinase) kinases than the immature Gln1-CX3CL1 in a time- and concentration-dependent manner. Furthermore, pGlu1-CX3CL1 affected the expression of CCL2, CX3CL1, and the adhesion molecule ICAM1/CD54 (intercellular adhesion molecule-1) inducing in higher expression level compared with its Gln1-variant in both HCASMCs and HUVECs. These results strongly suggest that QC-catalysed N-terminal pGlu formation of CX3CL1 is important for the stability or the interaction with its receptor and opens new insights into the function of QC in inflammation.